PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 007 SERUSA MATI - Aladin '; Zairul Antosa Zariul Antosa; Damanhuri Daud Damanhur Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Problem on this research was that student’s  achievement on social studies at grade four of SDN 007 Serusa Mati was still low. Student’s who completed 8 student’s (26,19%) and did not completed 22 studen’ts (80,95%)  with mean score of 70. This research was done to implement the Cooperative Learning type Make a Match. It was aimed at improving student’s achievement on Social Studies at the Four Graderes of SDN 007 Serusa Mati by using the Make a Match type . These results indicate that the first cycle replicates individual student mastery increased from a base score that is 8 people who completed (26.66%) increased by 22 to 30 students (82.95%). In the second cycle increases by 5 people (11.9%) from the first cycle to 39 students (92.85%). In the third cycle increases by 3 people (7.15%) of the cycles of the second cycle to 30 students (100%). In conclusion, the implementation of Cooperative Learning type Make a Match was able to Improve Student’s achievement on Social Studies at the Four Graderes of SDN 007 Serusa Mati. Keyword: Make a Match, the results of social studies.